Diversity of D-loop mitochondrial DNA (mtDNA) sequence in Bali and Sumba Ongole cattle breeds - Jakaria, J.; Musyaddad, T.; Rahayu, S.; Muladno, M.; Sumantri, C. (Journal of the Indonesian Tropical Animal Agriculture, 2019)
This study aimed to investigate the diversity of the complete sequence of D-loop mitochondrial DNA (mtDNA) in Bali and Sumba Ongole (SO) cattlebreeds. A total of 24 blood samples were collected from Bali cattle (19 heads) and SO cattle (5 heads), and were extracted and then analyzed to obtain the sequence of D-loop mt DNA.Multiple alignments of the whole sequence of D-loop mtDNA were determined using clustal W. Genetic distance was calculated using a p-distance method, while the genetic tree was constructed using neighbor-joining (NJ) based on MEGA 6. Haplotype number, haplotype diversity (Hd) and nucleotide diversity (Pi) were analyzed using DnaSP version 6. As a result, the sequence of D-loop mtDNA in Bali cattle (921-1119 bp) and SO cattle (913 bp) was reported to have 8 and 4 haplotypes. Hd and Pi of Bali cattle reached 0.625±0.139 and 0.0266±0.0145, respectively, which wwere different from that of SO cattle, namely 0.900±0.1610 and 0.0064±0.0015, respectively. Specifically, we found 22 bp-repetitive nucleotide in Bali cattle, existing 3-9 times with a length of 66-198 bp present in D-loop mtDNA. This unique feature did not exist in SO cattle. Genetic distance and genetic tree determined according to sequence in hypervariability (HV-1) region of D-loop mtDNA (166 bp) resulted in satisfied separation, successfully classifying Bos javanicus, Bos indicus, and Bos taurus cluster.